1993
DOI: 10.4141/cjas93-007
|View full text |Cite
|
Sign up to set email alerts
|

Eating and ruminating activities of cattle fed alfalfa or orchard-grass harvested at two stages of maturity

Abstract: NDF), (2) luzerne, floraison 50% (167oP8,47% NDF), (3) dactyle, anthdse (l7VoPB,56% NDF) ou (4) dactyle, post-anthdse (14% PB, 59 % NDF). Le temps pass6 i brouter 6tait le meme pour tous les r6gimes, soit 360 min j-', P > 0,05), ce qui fait que le NDF de la luzerne 6tait expos6 )r une mastication plus longue que celui du dactyle (P : 0,001) soit 167,8 contre 112,2 min kg-' NDF. Une plus grande proportion de la matidre sbche 6tait solubilis6e durant la phase d'alimentation i partir de la luzeme que du dactyle: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
6
11
1
Order By: Relevance
“…The value mean for the number of ruminated bolus per day was 324. Likewise, Beauchemin and Iwaasa (1993) observed from 350 to 397 ruminated bolus per day in Hereford heifers reared in pasture; which is close to the number found in this study.…”
Section: Diets Effectssupporting
confidence: 76%
“…The value mean for the number of ruminated bolus per day was 324. Likewise, Beauchemin and Iwaasa (1993) observed from 350 to 397 ruminated bolus per day in Hereford heifers reared in pasture; which is close to the number found in this study.…”
Section: Diets Effectssupporting
confidence: 76%
“…In this study, the rumination time reflected the intake of structural fibre in the diet as found by Beauchemin and Iwaasa (1993) in an experiment with alfalfa hay fed to heifers. The daily ruminating time tended to correlate with the duration of the ruminating periods indicating that increased rumination is obtained by longer periods and not by more periods as observed by Beauchemin and Iwaasa (1993). Beauchemin and Iwaasa (1993) also found an effect by harvest time of alfalfa hay on ruminating time in min/kg DMI but not in min/kg NDFI and number of JM/kg NDFI as seen in this experiment.…”
Section: Silagesmentioning
confidence: 99%
“…Therefore, the feed intake was higher at that treatment. Beauchemin and Iwaasa (1993) examined alfalfa hay at two maturity stages fed to heifers with no supplement of concentrate. In congruence with the present experiment, the NDFI was 0.54% and 0.68% of BW for early and late alfalfa hay, respectively.…”
Section: Silagesmentioning
confidence: 99%
See 1 more Smart Citation
“…the quantity of grass per bolus. Animals which are fed hay decrease the quantity per bolus with increasing forage maturity [3].…”
Section: The Effect Of the Stage Of Maturitymentioning
confidence: 99%